Internet-based peer support interventions for people living with HIV: A scoping review. - Stefanella Costa-Cordella; Aitana Grasso-Cladera; Alejandra Rossi; Javiera Duarte; Flavia Guiñazu; Claudia P Cortes (PLoS ONE)
Peer support interventions for people living with HIV and AIDS (PLWHA) are effective, but their associated time and material costs for the recipient and the health system make them reachable for only a small proportion of PLWHA. Internet-based interventions are an effective alternative for delivering psychosocial interventions for PLWHA as they are more accessible. Currently, no reviews are focusing on internet-based interventions with peer support components. This scoping review aims to map the existing literature on psychosocial interventions for PLWHA based on peer support and delivered through the internet. We conducted a systematic scoping review of academic literature following methodological guidelines for scoping reviews, and 28 articles met our criteria. We summarized the main characteristics of the digital peer support interventions for PLWHA and how they implemented peer support in a virtual environment. Overall the reported outcomes appeared promising, but more robust evidence is needed.